Scheduling and cost analysis program for project management - Che Mat Ismail (1989)
This .thesis describes the important elements involved in the project management, especially of the construction works. Based on extensive literature study,a project management package is designed, which can be run on microcomputers. The methods are based on the network analysis techniques and they are menu driven. In other words, the end user can enter or update the record data and operate various management activities found in the package via the terminal through menu displays. The package is capable to perform the scheduling of the activities of the project and the calculation of various costs involved. Besides those, the package also permits the end user to print various types of outputs. In order to meet the present project environment, the package allows direct integration of all project information stored in the database files. The package makes use of the dBase III software facility which contribute a relational database structure. Consequently, the project control is more manageable and forward looking. Hence the decisions or corrective actions taken by the project management team are more appropriate and can produce the better outcome of the project implementation.